Assessing Changes in Adolescents' Sleep Characteristics and Dietary Quality in the START Study, a Natural Experiment on Delayed School Start Time Policies. Issue 9 (4th June 2021) - Full, Kelsie M; Berger, Aaron T; Erickson, Darin; Berry, Kaitlyn M; Laska, Melissa N; Lenk, Kathleen M; Iber, Conrad; Redline, Susan; Widome, Rachel
ABSTRACT: Background: Sleep duration, quality, and timing may influence dietary quality. In adults, poor dietary quality is a risk factor for numerous chronic diseases. It is unclear how these various sleep domains influence adolescents' diets because prior population-based studies have not effectively manipulated sleep, did not include objective sleep measures, and had short follow-up times. Objectives: The objectives of this study were to examine 1 ) how adolescent sleep characteristics relate to dietary quality; and 2 ) how delay in high school start times (which lengthened sleep duration) affects dietary quality over 2 y. Methods: In the START study, adolescents (grades 9–11, n  = 423) attending 5 high schools in the Minneapolis, Minnesota metropolitan area were annually assessed in 3 waves (2016–2018). At Baseline, all schools started "early" (07:30 or 07:45). From Follow-up 1 through Follow-up 2, 2 "policy change schools" shifted to later start times (to 08:20 and 08:50). Three "comparison schools" maintained their early start throughout. Sleep characteristics were measured with actigraphy. Mixed-effect regression models were used to examine cross-sectional and longitudinal associations of sleep characteristics with dietary quality, and school start time policy change with dietary quality change. Results: Cross-sectionally, later sleep midpoint and onset were associated with dietary quality scores 1.6–1.7 lower (both P  < 0.05). However, no prospective associations were observed between sleep characteristics and dietary quality in longitudinal models. Shifting to later school start time tended to be associated with a 2.4-point increase in dietary quality score ( P =  0.09) at Follow-up 1, but was not associated with change in dietary quality scores at Follow-up 2 ( P =  0.35). Conclusions: High school students attending delayed-start schools maintained better dietary quality than students in comparison schools; however, differences were not statistically significant. Overall study findings highlight the complexity of the relation between sleep behavior and diet in adolescence.